Medical Malpractice as a Criminal Offense under the Health Law: An Islamic Criminal Law Perspective - Hesnikmah Aulia Syifa Assyahra; Yayan Muhamad Royani; Enceng Arif Faizal (Jurisprudensi: Jurnal Ilmu Syariah, Perundang-Undangan dan Ekonomi Islam, 2026)
Ideally, the regulation of medical malpractice should ensure patient protection while maintaining the professionalism of medical personnel through a balanced justice mechanism. However, in reality, the provisions of Article 440 of Law Number 17 of 2023 on Health remain oriented toward retributive punishment in the form of imprisonment and fines, without accommodating direct victim recovery, so that substantive justice has not been fully achieved. This study aims to analyze the elements of medical malpractice as a criminal offense within the Health Law and to examine it from the perspective of Islamic criminal law. This article is categorized as a qualitative library research, and the methodology used is normative legal study. The results of the study indicate that: First, medical malpractice under the Health Law requires the presence of gross negligence by medical personnel resulting in serious injury or death, with criminal sanctions differentiated based on the consequences. Second, Islamic criminal law views medical negligence as al-khatha’ or qatl al-khata’, with sanctions in the form of diyat, kafarat, and ta’zir, which emphasize victim recovery and the moral responsibility of the offender.